P64 An in-silico investigation of DNA repair gene variation in the mycobacteroides abscessus subspecies abscessus ST26 clonal lineage. (12th November 2019) - Kenna, D; Mustafa, N; Peters, C; Turton, J; Langley, RJ
Abstract : There is growing concern about the increasing prevalence of Mycobacteroides abscessus subspecies among children and adults with cystic fibrosis (CF). Reasons for this increase include improved identification and surveillance, antibiotic resistance and in some cases, transmission. In the CF population various typing methods have highlighted the prevalence of international clonal lineages such as ST1 and ST26, shown to be associated with chronic infection, increased inflammatory response and enhanced intracellular survival in macrophages. We examined whole genome sequences (WGS) of three paediatric CF ST26 isolates from a single CF centre for the presence of mismatch and DNA repair mutations which might contribute to the success of this lineage, based on homology to Mycobacterium tuberculosis genes. Of 46 genes examined, 20 had 100% amino acid identity with those of the type strain CIP 104536, while 26 had ≤99% identity. All three isolates had identical gene profiles. Eleven candidate genes coding for MutY, UrvD2, PolC, RecF, RecB, RecB exodeoxyribonuclease V beta chain, Ung, DnaE, MazG, Mfd and Ssb-1 with ≤99% identity to CIP 104536 were examined in more detail. Of these, MazG and Mfd had six and seven amino acid changes respectively, compared to CIP 104536, and exhibited variation among 17 publicly-available WGS. The MazG mutations were found in six other ST26 genomes but in only one other ST (ST82), suggesting they are particularly prevalent in ST26. All seven Mfd mutations were only found in two of six ST26 genomes, and in none of the other STs, suggesting these mutations are more prevalent in ST26, but that intra-lineage variation exists. M. tuberculosis studies have shown that deletion of MazG results in a mutator phenotype during oxidative stress and stationary phase, and in increased survival under hypoxic conditions compared to the wild-type. In Bacillus sp., Mfd ('Mutation frequency decline') works in combination with the RecBC repair pathway protecting the bacteria against the genotoxic effect of nitrite. Further experimentation is needed to examine any effects on bacterial survival and mutation rates.